Malpractice and system of expertise in anaesthetic procedures in Turkey - Özdemir, M. Hakan; Çekin, Necmi; Can, I. Özgür; Hilal, Ahmet (Forensic science international, 2005)
Deaths which occur during the administration of anaesthetics require medicolegal investigations. The objective of this study is to form a database for future comparisons related to anaesthetic-associated malpractice claims and also to investigate the system of expertise, pertaining to such procedures. The decisions of the Supreme Health Council, whose expert opinion is requested by legal authorities (judges, prosecutors) for health workers brought to trial in a criminal court, were examined retrospectively over the period 1995–1999. In 21 (2.3%) of the 888 decision reports prepared by the council the team members (the anaesthologist, the anaesthetic assistant, the anaesthetic technician, the nurse) were directly interrogated. Data concerning these 21 council decisions were evaluated within the scope of this study. It was found that 57% of the 21 decisions were related to medical procedures carried out in state hospitals. Of the 21 cases, 62% were males, 38% females. General anaesthesia was applied to 19 of the cases while one received regional (local) anaesthesia and one axillary blockade. Twenty died of complications associated with anaesthesia. Autopsy was performed on 11 (55%) of the dead. Health workers were found to have different degrees of liability in the 16 (76%) of the 21 decision reports. In their medical practices, anaesthologists, like other specialists, are subject to legal procedures in the country where they perform their duties, to national and international principles of ethics, and to diagnostic and curative standards/procedures relevant to the scientific level of the country concerned. In anaesthetic malpractice claims, certain standards need to be followed in inquiries and approaches so as to determine the real reasons behind the disabilities and/or deaths which occur. In order that sound evaluations could be made in such cases, the experts as well as the system of expertise should be efficient and authorized.